A new biofilm-associated colicin with increased efficiency against biofilm bacteria - Rendueles, Olaya (Nature Publishing Group, 2014)
Formation of bacterial biofilm communities leads to profound physiological modifications and increased physical and metabolic exchanges between bacteria. It was previously shown that bioactive molecules produced within the biofilm environment contribute to bacterial interactions. Here we describe new pore-forming colicin R, specifically produced in biofilms formed by the natural isolate Escherichia coli ROAR029 but that cannot be detected under planktonic culture conditions. We demonstrate that an increased SOS stress response within mature biofilms induces SOS-dependent colicin R expression. We provide evidence that colicin R displays increased activity against E. coli strains that have a reduced lipopolysaccharide length, such as the pathogenic enteroaggregative E. coli LF82 clinical isolate, therefore pointing to lipopolysaccharide size as an important determinant for resistance to colicins. We show that colicin R toxicity toward E. coli LF82 is increased under biofilm conditions compared with planktonic susceptibility and that release of colicin R confers a strong competitive advantage in mixed biofilms by rapidly outcompeting sensitive neighboring bacteria. This work identifies the first biofilm-associated colicin that preferentially targets biofilm bacteria. Furthermore, it indicates that the study of antagonistic molecules produced in biofilm and multispecies contexts could reveal unsuspected, ecologically relevant bacterial interactions influencing population dynamics in natural environments.